Procedural Knowledge, Cognitive Load and their Correlation with Performance of Productive Skills for Iraqi EFL learners - Ayed, Zubaida Samir; Yahya, Nagham Q. (Journal of Tikrit University for Humanities, 2024)
Procedural knowledge that involves understanding how to perform tasks effectively, and cognitive load managing can be associated with the production of productive language skills. The current study is a correlational study, which aims to find out the type of connections between the learners' ability to utilize procedural knowledge, managing cognitive load, and the producing language. The sample of the study is 240 students at the third-year of English Department at Tikrit University in the academic year 2022/2023. The data is gathered through using two tools, a questionnaire to identify students' cognitive load types and two diagnostic tests to assess the level of procedural knowledge, cognitive load and productive skills' performance. Results of the study show that there is a significant correlation between students' procedural knowledge and writing skill, and there is a significant correlation between students' cognitive load and productive skills, that students response in germane cognitive load has the highest mean score and that the correlation is positive. The statistical means show also that there is no significant correlation between students' procedural knowledge and speaking skill. In the light of these results, some conclusions, recommendations and suggestions for further studies are presented.